Beta Palmitate Improves Bone Length and Quality during Catch-Up Growth in Young Rats - Meytal Bar-Maisels (Nutrients, 2017)
Palmitic acid (PA) is the most abundant saturated fatty acid in human milk, where it is heavily concentrated in the sn-2-position (termed beta palmitate, BPA) and as such is conserved in all women, regardless of their diet or ethnicity, indicating its physiological and metabolic importance. We hypothesized that BPA improves the efficiency of nutrition-induced catch up growth as compared to sn-1,3 PA, which is present in vegetable oil. Pre-pubertal male rats were subjected to a 17 days food restriction followed by re-feeding for nine days with 1,3 PA or BPA-containing diets. We measured bone length, epiphyseal growth plate height (EGP, histology), bone quality (micro-CT and 3-point bending assay), and gene expression (Affymetrix). The BPA-containing diet improved most growth parameters: humeri length and EGP height were greater in the BPA-fed animals. Further analysis of the EGP revealed that the hypertrophic zone was significantly higher in the BPA group. In addition, Affymetrix analysis revealed that the diet affected the expression of several genes in the liver and EGP. Despite the very subtle difference between the diets and the short re-feeding period, we found a small but significant improvement in most growth parameters in the BPA-fed rats. This pre-clinical study may have important implications, especially for children with growth disorders and children with special nutritional needs.